2015
DOI: 10.1891/2156-5287.5.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Dutch Midwives’ Behavior and Determinants in Promoting Healthy Gestational Weight Gain, Phase 1: A Qualitative Approach

Abstract: BACKGROUND: A significant contributor to the global threat of obesity is excessive gestational weight gain (GWG). The aim of this article is to explore Dutch primary care midwives’ behaviors in promoting healthy GWG.METHODS: We used the attitude–social influence–self-efficacy (ASE) model to guide interviews with a purposive sample of 6 midwives working in primary care.RESULTS: Midwives reported activities in 3 areas related to GWG: GWG monitoring (weighing and discussing GWG), diet education, and to a lesser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…A decline in PA was associated with GWG above the guidelines. Our qualitative study of six community midwives showed that midwives did monitor GWG (weighing and discussing GWG), offered education about diet, and, to a lesser degree, offered education about healthy PA. 204 Behavioural determinants, originating from the ASE model, 258 were confirmed and other relevant themes, including midwives' perception on their role in health promotion were added to our hypothetical model explaining midwives' behaviour in respect to promoting healthy GWG.…”
Section: Step I Needs Assessmentmentioning
confidence: 90%
See 4 more Smart Citations
“…A decline in PA was associated with GWG above the guidelines. Our qualitative study of six community midwives showed that midwives did monitor GWG (weighing and discussing GWG), offered education about diet, and, to a lesser degree, offered education about healthy PA. 204 Behavioural determinants, originating from the ASE model, 258 were confirmed and other relevant themes, including midwives' perception on their role in health promotion were added to our hypothetical model explaining midwives' behaviour in respect to promoting healthy GWG.…”
Section: Step I Needs Assessmentmentioning
confidence: 90%
“…183 Antenatal care providers, including midwives, confirm they give low priority to motivating pregnant women to have healthy levels of PA and they often give women advice to slow down. 185,[202][203][204][205] Since prenatal PA is associated with better outcomes, 22, 159, 173-176 future interventions should aim to increase knowledge in both midwives and pregnant women and should emphasize the importance of healthy PA (e.g., moderate active activities including walking, biking, swimming) during pregnancy. Midwives may also advise women to slow down because of their concern about the growing psychological complaints women experience.…”
Section: -201mentioning
confidence: 99%
See 3 more Smart Citations